GAMBARAN PENGETAHUAN IBU HAMIL TENTANG PERUBAHAN PSIKOLOGIS KEHAMILAN DI WILAYAH KERJA PUSKESMAS PARIAMAN - Rahmawati, Lisa; Ningsih, Mahdalena Prihatin (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
Based on the WHO data, there are 352 from 2,321 primigravida pregnant women who complained of feer as big as 36%, anxious 42% and unconfident 22% in the pregnancy. Indonesian health demography survey results in 2012 showed that there were 50 from 850 primigravida pregnant women who complained of stress as big as 20%, anxious 35%, and fear 45% during pregnancy on February 2015, 8 from 15 interviwee women didn’t know about the pshycological changing and they complained not confident about changes in the body. The objective of the research is to know the description of pregnant women’s knowledge about psychological changes during the pregnancy in Puskesmas Pariaman Working Area. The type of this research is quantitative with analytic descriptive research design. Research population is all pregnant women that come for pregnancy check in Puskesmas Pariaman. Accidental sampling is used as sampling technique with 36 people. Univariate is chosed in data precessing. Univariate result showed that 63,9% have low knowledge level in psychological change for first trimester, 63,9% for second and third trimester respectively, and 52,8% have low knowledge level about the impact of psychological changes to the pregnancy. Pregnant women is suggessed to expand the knowledge released to pregnancy and birth, typing to be open to the social environment released to their pregnancy. These things are required to give knowledge to pregnant women so that they can understand physical and psychological condition during the pregnancy. Keywords: Psychological, pregnancy